2008
DOI: 10.1155/2008/767623
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance: A Proinflammatory State Mediated by Lipid‐Induced Signaling Dysfunction and Involved in Atherosclerotic Plaque Instability

Abstract: The dysregulation of the insulin-glucose axis represents the crucial event in insulin resistance syndrome. Insulin resistance increases atherogenesis and atherosclerotic plaque instability by inducing proinflammatory activities on vascular and immune cells. This condition characterizes several diseases, such as type 2 diabetes, impaired glucose tolerance (IGT), impaired fasting glucose (IFG), obesity, hypertension, dyslipidemia, and other endocrinopathies, but also cancer. Recent studies suggest that the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 152 publications
1
53
0
2
Order By: Relevance
“…Considering the pivotal roles of VSMC apoptosis [7][8][9][10][11][12] and the elevated plasma FFA levels [4,5] in atherosclerotic plaque ruptures, we investigated the potential effects of wogonin on palmitate-induced VSMC apoptosis. The serum-starved VSMCs were treated with different doses of wogonin for the desired time in the presence of 0.75 mmol/L palmitate for 24 h. As shown in Figure 2A and 2B, wogonin significantly attenuated the palmitateinduced apoptosis in a dose-and time-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the pivotal roles of VSMC apoptosis [7][8][9][10][11][12] and the elevated plasma FFA levels [4,5] in atherosclerotic plaque ruptures, we investigated the potential effects of wogonin on palmitate-induced VSMC apoptosis. The serum-starved VSMCs were treated with different doses of wogonin for the desired time in the presence of 0.75 mmol/L palmitate for 24 h. As shown in Figure 2A and 2B, wogonin significantly attenuated the palmitateinduced apoptosis in a dose-and time-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Increased free fatty acid (FFA) levels in the plasma caused lipotoxicity, which is a hallmark of diabetes mellitus and leads to an increased risk of atherosclerosis and cardiovascular diseases [1][2][3] . Strong evidence has suggested that elevated FFA levels in the plasma enhance the intracellular accumulation of diacylglycerol (DAG), which leads to the activation of protein kinase Cs (PKCs), inhibitor kappaB kinase (IKK), or c-Jun N-terminal kinase (JNK), resulting in atherosclerotic plaque development and instability [4,5] . Therefore, the plasma FFA and intracellular DAG levels represent selective targets to prevent atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin release is enhanced more by SFA than PUFA. The mechanism of this β-cell response is not known, although it has been suggested that an unknown FA metabolite (receptor) resulting from insulin action through SREBP-1c is involved 220 . A study showed that postprandial β-cell function and insulin sensitivity improved with increased proportion of MFA to SFA in dietary fat 221 .…”
Section: Insulin Sensitivity and The Metabolic Syndromementioning
confidence: 99%
“…atherosclerosis; insulin resistance CHRONIC ALTERATIONS IN LIPID PROFILE have been associated with high circulating levels and resistance to insulin, a condition favoring atherogenesis and acute cardiovascular events (7,9,20). Importantly, the exposure to high plasma levels of free fatty acids (FFAs) might be particularly related to hyperisulinemia (20).…”
mentioning
confidence: 99%
“…Importantly, the exposure to high plasma levels of free fatty acids (FFAs) might be particularly related to hyperisulinemia (20). On the other hand, FFAs have been shown to potentially influence insulin-mediated functions by interfering with insulin receptor activation and downstream intracellular signaling pathways (20).…”
mentioning
confidence: 99%